Unboxing experience afetando a satisfação do recebimento de presentes quando moderado pela expectativa do conteúdo - MORAES, Paula Luize Silva (Universidade Federal do Pará, 2025)
This study aims to analyze the moderating effect of the Expectation of the gift, in relation to the Unboxing Experience and their satisfaction with the gift when receiving it. The aim is to identify different perceptions in the context of gift packaging, bringing a consumption experience beyond the present itself, showing all the charm in unwrapping a received content, and all its subjectivity in the perceived value, thus constituting a mediation of the relationship between the Unboxing Experience and satisfaction with the gift. The methodological conduction was carried out through a quantitative experiment with a 2 x 2 factorial study, presenting perceived value as a mediating variable and expectation with the present as a moderating variable. Data analysis showed that the perceived value acts as a mediator between the Unboxing Experience and the satisfaction of the gift, which was proven by describing that the perception of value arising from the unboxing experience further increases satisfaction due to the specific expectation of receiving the gift, that the consumer will have generating an increase in the perceived value with the consumption experience